2016
DOI: 10.1016/j.soncn.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention: HPV Vaccination

Abstract: Objectives To provide an overview of Human Papillomavirus (HPV) vaccination as cancer prevention with current strategies that nurses can use to help patients and parents overcome barriers to HPV vaccination. Data Sources Peer reviewed literature, presentation abstracts, and current immunization recommendations from the Advisory Council on Immunization Practice (ACIP). Conclusion Nurses can help prevent cancer by encouraging HPV vaccination during routine immunization and make HPV vaccination normal and rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
0
22
0
4
Order By: Relevance
“…Nowadays, vaccination is one of the most effective and economical strategies for humans and animals to control and prevent the spread of infectious diseases. It is worth noting that, in recent years, with the advancement of immunology, biotechnology, and nanotechnology, etc., some intractable cancers have been included in the scope of vaccination targets, and great therapeutic effects in some patients have been achieved [199,200]. Traditionally, vaccines are mainly delivered by intramuscular injection, but this route generally cannot induce effective mucosal immunity.…”
Section: Applications Of Chitosan Derivative Nanoparticles In Mucosalmentioning
confidence: 99%
“…Nowadays, vaccination is one of the most effective and economical strategies for humans and animals to control and prevent the spread of infectious diseases. It is worth noting that, in recent years, with the advancement of immunology, biotechnology, and nanotechnology, etc., some intractable cancers have been included in the scope of vaccination targets, and great therapeutic effects in some patients have been achieved [199,200]. Traditionally, vaccines are mainly delivered by intramuscular injection, but this route generally cannot induce effective mucosal immunity.…”
Section: Applications Of Chitosan Derivative Nanoparticles In Mucosalmentioning
confidence: 99%
“…Each year, the Human Papillomavirus (HPV) causes about 34,800 new cancer cases in the United States [1]. HPV vaccination among adolescents offers an important opportunity to prevent cervical and other cancers in adulthood [2]. However, across the US, HPV vaccine uptake among adolescents remains low, with only 54% of 13-17 years old completing the recommended course of the vaccine as of 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified that health professionals play an important role in vaccines uptake. Moreover, there is a lack of initiatives to improve education among undergraduate healthcare students about HPV infection, consequences, and prevention [10]. For a large majority of these young adults (women or men), the internet is the main and only source of information.…”
Section: Introductionmentioning
confidence: 99%